2009
DOI: 10.1073/pnas.0910986107
|View full text |Cite
|
Sign up to set email alerts
|

VGLUT2 in dopamine neurons is required for psychostimulant-induced behavioral activation

Abstract: The "One neuron-one neurotransmitter" concept has been challenged frequently during the last three decades, and the coexistence of neurotransmitters in individual neurons is now regarded as a common phenomenon. The functional significance of neurotransmitter coexistence is, however, less well understood. Several studies have shown that a subpopulation of dopamine (DA) neurons in the ventral tegmental area (VTA) expresses the vesicular glutamate transporter 2 (VGLUT2) and has been suggested to use glutamate as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
152
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 119 publications
(165 citation statements)
references
References 37 publications
13
152
0
Order By: Relevance
“…Elevated self-administration of high-sucrose, but not low-sucrose, food To test the functional implications for VGLUT2 in DA neurons (hereafter referred to as VGLUT2/DA), we studied voluntary consumption of rewarding substances in our previously described conditional Vglut2 f/f;DAT-Cre mouse line (Birgner et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Elevated self-administration of high-sucrose, but not low-sucrose, food To test the functional implications for VGLUT2 in DA neurons (hereafter referred to as VGLUT2/DA), we studied voluntary consumption of rewarding substances in our previously described conditional Vglut2 f/f;DAT-Cre mouse line (Birgner et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…By crossing Vglut2 f/f mice (Wallén-Mackenzie et al, 2006;Wallén-Mackenzie et al, 2009) with DAT-Cre mice (Ekstrand et al, 2007), as described previously (Birgner et al, 2010), both Vglut2 f/f;DAT-Cre cKO and Vglut2 f/f control (Ctrl) mice (which do not express the DAT-Cre transgene and therefore have normal Vglut2 expression) were produced in the same litters. Thus, cKO and Ctrl mice were of the same genetic background, a hybrid of C57/BL6 and Sv129.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Long-standing evidence, primarily from cultured DA neurons, had indicated that glutamate could be synthesized and released by DA neurons [147,148]. Using optogenetic methods with selective expression of channelrhodopsin (ChR2) in DA neurons, several groups have now shown that glutamate released from DA axons produces glutamate receptor-dependent excitatory postsynaptic currents in striatal neurons in ex vivo slices [149][150][151][152][153][154] and mediates behavioural consequences in vivo [155]. Similar methods have shown that co-release of GABA from DA axons produces GABA A receptor-dependent IPSCs in striatal neurons, although DA neurons do not synthesize GABA but rather obtain it via plasma membrane uptake [152,156].…”
Section: Modulation Of Somatodendritic Dopamine Release By Synaptic Imentioning
confidence: 99%